TINJAUAN YURIDIS TENTANG PENERAPAN RESTORATIVE JUSTICE PADA KASUS TINDAK PIDANA ANAK DI TINJAU DARI UU NO. 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK - Novia Nur Azizaturohma (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT In function of the House of Representatives (DPRD) of the Kutai regency Legislation efforts in improving the Rule of Law by Law No. 32 Year 2004 on Regional Government, our attention will be focused on the function Legislation Legislative Council (DPRD) as a legal product penyususun institution (Regulation) as well as the role of the Regional Representatives Council Kutai regency in the preparation of the Regional RegulationIn connection with the writer pour in the thesis, the author uses research methods normative juridical, sociological juridical, technical data collection either direct observation or collection of documents related to the functioning Legislation Legislative Council (DPRD) Kutai regencyAs we know, Functions Legislation Legislative Council (DPRD) Kutai regency had not run all that needs fixing good.Alot both structurally and individual.penulis find a lot of irregularities by the Council Members should seek Rule of Law for the community but in fact busier Councillors seek the interest of the party so it is not wrong if the Products Law (Regulation) often called the Political ProductSo far found a wide range of obstacles that inhibit the function of Legislation Legislative Council (DPRD) ranging from internal factors, which are external to the individual and the institution of the People's Representative Council (DPRD) was sendiri.berkaitan with Tasks and Functions, member of Legislative Council must understand the real conditions in society that policies and regulations can be made to have accurate power for the manufacture masyarakat.sehubungan with function legislation Regulation (Regulation), then the House of Representatives (DPRD) should be subject to the Law No. 32 Year 2004 on Local Government and the reference to the Minister of Home Affairs Regulation No. 53 Year 2011 on Product Development Law (Regulation)